Participant characteristics and HIV risk behaviors among individuals entering integrated buprenorphine/naloxone and HIV care. - Chaudhry, Amina A; Botsko, Michael; Weiss, Linda; Egan, James E; Mitty, Jennifer; Estrada, Barbara; Lucas, Gregory M; Woodson, Tanita; Flanigan, Timothy P; Fiellin, David A (Journal of acquired immune deficiency syndromes (1999), 2011)
This study was part of a national, multisite demonstration project evaluating the impact of integrated buprenorphine/naloxone treatment and HIV care. The goals of this study were to describe the baseline demographic, clinical, and substance use characteristics of the participants and to explore HIV transmission risk behaviors in this group.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Buprenorphine; Cross-Sectional Studies; Female; HIV Infections; Humans; Male; Methadone; Middle Aged; Naloxone; Narcotic Antagonists; Needle Sharing; Odds Ratio; Opiate Substitution Treatment; Opioid-Related Disorders; Risk-Taking; Unsafe Sex